A RESEARCH OF BRAIN DRAIN IN SOCIAL SCIENCES IN THE CONTEXT OF MASLOW HIERARCHY: THE CASE OF TURKİYE (Third Sector Social Economic Review, 2023)
The aim of this study is to identify the push and pull factors influencing the emigration of Turkish citizens who have pursued education abroad or continued their lives abroad after completing their education, within the framework of Maslow's Hierarchy of Needs in the field of social sciences. For this purpose, semi-structured interviews were conducted with thirty-six (36) participants residing in the United States, Canada, and European countries, among the targeted group. The snowball sampling method was employed to increase the number of participants in the sample. The data obtained from the interviews were evaluated through content analysis. The findings reveal that within Maslow's Hierarchy of Needs, social status emerged as an attractive factor, while security emerged as a driving factor, indicating significant indicators. Furthermore, it was determined that university habitus plays a critical role for brain drain, highlighting the necessity for university-affiliated units to assume an effective role. In this context, policy recommendations were developed. It is expected that this study will contribute by associating the subject of qualified migration in the context of social sciences with Maslow's Hierarchy of Needs and pointing to the role of university components in providing solutions to the subject matter in its discourse. It is expected that this study will contribute by associating the topic of qualified migration in the context of social sciences with Maslow's Hierarchy of Needs and pointing out the role of university components in proposing solutions to the subject matter.
Keywords: Migration; brain drain; skilled migration; Maslow hierarchy; university.